Complications of Diagnostic Cardiac Catheterization in National Heart Centre, Nepal - Maskey, Arun; Regmi, Shyam Raj; Dubey, Laxman; Bhatt, Yadav; Malla, Rabi; K C, Man Bahadur; Sharma, Deewakar; Limbu, Yuba Raj; Rajbhandari, Rajib (Nepalese Heart Journal, 2017)
Cardiac Catheterization for diagnostic has been routinely used for the last few years in national heart centre in Nepal. Complications have been recognized as an important factor in morbidity and mortality after diagnostic catheterization. Improvements of technique and technology have reduced the morbidity of routine diagnostic catheterization, but occasional mortality seems to be unavoidable. A total of 6074 consecutive diagnostic cardiac diagnostic cardiac catheterization performed in Shahid Gangalal National Heart Centre, Kathmandu, Nepal between 2004 to 2008 were evaluated for their complications. Among them 4584 (75.46%) were coronary angiogram. 894 (14.71%) were right heart study and 596 (9.81%) were left heart study. There were 5 deaths (0.09%). Four deaths occurred following coronary angiogram and I death following left heart study in a 3 years old boy with Tetralogy of Fallot. Vascular complications occurred in 20(0.33% patients) with groin haematoma in 8 (0.13%), pseudoaneurysm in 5 (0.09%), arterrio venous fistula in 3 (0.05%) and femoral artery thrombosis in 4 (0.06%) patients. Contrast allergy occurred in 7(0.12%), cerebrovascular complication in 3 (0.05%), vasovagal reaction in 5 (0.09%) and pyrogen reaction in 10 (0.16%) of patients. The diagnostic cardiac catheterization in national heart centre has acceptable low rate of complication which includes death.